METHODOLOGY FOR THE DEVELOPMENT OF CREATIVE ABILITIES OF STUDENTS IN ELEMENTARY SCHOOL MATHEMATICS LESSONS - Noriyeva Shohista Furqatovna; Abrorkhanova Kamola Abrorkhan daughter (American Journals, 2023)
This article contains resources that can be used to develop creative abilities in elementary school students. This article covers the problems and solutions to the organization of independent creative thinking of primary school teachers. In the preparation of the future teacher, the peculiarities of performing work in the formation of creativity in primary school students are revealed, and effective forms of improving creativeness, skills and competencies in primary school students are analyzed. On the basis of the opinions advanced in the article, an attempt was made to provide information that teachers and parents could benefit for themselves based on the relevant sources.
Keywords: pedagogy, creative activity, skill, morality, interactive method, education, methodology, thinking, creative, sign, exercise, thinking, creativity, freedom, childhood, problem assignment.